Integrative multiomics reveals common endotypes across PSEN1, PSEN2, and APP mutations in familial Alzheimer’s disease - Phoebe Valdes; Andrew B. Caldwell; Qing Liu; Michael Q. Fitzgerald; Srinivasan Ramachandran; Celeste M. Karch; Dominantly Inherited Alzheimer Network (DIAN); Douglas R. Galasko; Shauna H. Yuan; Steven L. Wagner; Shankar Subramaniam (Alzheimer’s Research & Therapy)
Abstract Background PSEN1, PSEN2, and APP mutations cause Alzheimer’s disease (AD) with an early age at onset (AAO) and progressive cognitive decline. PSEN1 mutations are more common and generally have an earlier AAO; however, certain PSEN1 mutations cause a later AAO, similar to those observed in PSEN2 and APP. Methods We examined whether common disease endotypes exist across these mutations with a later AAO (~ 55 years) using hiPSC-derived neurons from familial Alzheimer’s disease (FAD) patients harboring mutations in PSEN1 A79V , PSEN2 N141I , and APP V717I and mechanistically characterized by integrating RNA-seq and ATAC-seq. Results We identified common disease endotypes, such as dedifferentiation, dysregulation of synaptic signaling, repression of mitochondrial function and metabolism, and inflammation. We ascertained the master transcriptional regulators associated with these endotypes, including REST, ASCL1, and ZIC family members (activation), and NRF1 (repression). Conclusions FAD mutations share common regulatory changes within endotypes with varying severity, resulting in reversion to a less-differentiated state. The regulatory mechanisms described offer potential targets for therapeutic interventions.